Up‐regulation of A20 gene expression in peripheral blood mononuclear cells is associated with acute‐on‐chronic hepatitis B liver failure. Issue 3 (24th September 2015) - Fan, Y.‐C.; Sun, Y.‐Y.; Wang, N.; Xiao, X.‐Y.; Wang, K.
Summary: Aberrant immunity contributes to the pathogenesis of acute‐on‐chronic hepatitis B liver failure (ACHBLF), and A20 is a newly identified negative regulatory molecule of the immune response. However, no data have been reported for the role of A20 in ACHBLF. This study aimed to investigate A20 mRNA expression in ACHBLF and to determine the potential of A20 as a biomarker for the prognosis of ACHBLF. Quantitative real‐time polymerase chain reaction (qPCR) was used to measure the mRNA expression of A20 in peripheral blood mononuclear cells (PBMCs) from 137 ACHBLF patients, 105 chronic hepatitis B (CHB) and 35 healthy controls (HCs). A secondary cohort with 37 ACHBLF patients was set up as validation data set. The plasma levels of interleukin (IL)‐1 β, IL‐6 and IL‐10 were determined using enzyme‐linked immunosorbent assay (ELISA). Receiver‐operating characteristic (ROC) curves were used to determine the predictive value of A20 for the prognosis of ACHBLF patients. A20 mRNA expression in ACHBLF was significantly higher compared with CHB and HCs. In ACHBLF patients, A20 mRNA was closely associated with total bilirubin, albumin, international normalized ratio, prothrombin time activity and model for end‐stage liver disease. Furthermore, A20 mRNA was significantly correlated with IL‐6 and IL‐10. An optimal cut‐off value of 12.32 for A20 mRNA had significant power in discriminating survival or death in ACHBLF patients. In conclusion, our results suggest that the up‐regulation of the A20 gene might contribute to the severity of ACHBLF and A20 mRNA level might be a potential predictor for the prognosis of ACHBLF.